Faktor-Faktor yang Mempengaruhi Kinerja Dosen - Herawati, Jajuk; Rinofah, Risal (Universitas PGRI Yogyakarta, 2019)
Lecturers are professionals as well as scientists who are obliged to carry out the Tri Dharma of the college (Teaching, Research and Community Service). The performance of lecturers in the three dharma has an impact on the quality of higher education and also the development of the academic career of lecturers. However, the fact that was observed in FE UST, some lecturers spent more of their service in the teaching field only, while the implementation of research (especially the published ones) was minimal and only to meet the minimum standards of its obligations. Based on the literature review the factors that influence the performance of lecturers include Motivation, Competence and Commitment. The test results concluded that only the lecturers' motivation was influential, while competence and commitment had no effect.